The Analysis of Urban Farming Potential in Port Dickson for Food Security amid COVID-19 Pandemic - Noor Atiqah, Sanudin; Mohd Yazid, Mohd Yunos; Emran@Zahrin, Mohamad Taram (INTI International University, 2022)
COVID-19 pandemic and Movement Control Order (MCO) have resulted in a higher percentage of retrenchment, unpaid leave, or reduced wages, especially for the personnel in tourism and hospitality sectors under the B40 and M40 groups. With reduced household income, more families fell into a hard time and faced difficulties obtaining fresh goods such as vegetables with the amount of money left in hand. The study targeted to locate the potential locations in Port Dickson to be developed into urban farming and followed by the best approach of urban farming analyzed according to different site characters. A case study approach was adopted with two techniques, namely mapping analysis for Port Dickson's potential green spaces and interviews with urban farming experts to validate the findings. The findings recognized multiple approaches of urban farming subjected to different site characters and contextual forms. The study provides recommendations on strategies to accomplish a resilient food system embedding sustainability to correspond with Sustainable Development Goals (SDG) 2030, efficient land management for urban farms, empowering knowledge, and entrepreneurship of urban farming food production for individuals and communities.